Rabbit, run. - Updike, John (Knopf, 1960)
Twenty-two-year-old Rabbit Angstrom is a salesman in a local department store, father of a preschool-age son, and husband to an alcoholic wife who was his second-best high school sweetheart. The squalor and tragedy of their lives reminds us that salvation is a personal undertaking.